Designing and Implementing a Privacy Preserving Record Linkage Protocol. (2018) - Gee, Tom; Behan, Brendan; Lefaivre, Shannon; Azimaee, Mahmoud; Dharsee, Moyez; Emam, Khaled El; Yang, Julie; Vaccarino, Anthony; Evans, Kenneth; Victor, J. Charles; Theriault, Elizabeth
No abstract available